Prediction of Preterm Delivery Using Serum Ischemia Modified Albumin, Biglycan, and Decorin Levels in Women with Threatened Preterm Labor - Ismail Biyik; Cenk Soysal; Ozlem Ulas Onur Ince; Sinem Durmus; Efser Oztas; Nadi Keskin; Ozben Ozden Isiklar; Oğuz Han Karaagac; Remise Gelisgen; Hafize Uzun (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective The serum ischemia modified albumin (IMA), biglycan, and decorin levels of pregnant women who were hospitalized for threatened preterm labor were measured. Methods Fifty-one consecutive pregnant women with a single pregnancy between the 24th and 36th weeks with a diagnosis of threatened preterm labor were included in the present prospective cohort study. Results As a result of multivariate logistic regression analysis for predicting preterm delivery within 24 hours, 48 hours, 7 days, 14 days, ≤ 35 gestational weeks, and ≤ 37 gestational weeks after admission, area under the curve (AUC) (95% confidence interval [CI[) values were 0.95 (0.89-1.00), 0.93 (0.86-0.99), 0.91 (0.83-0.98), 0.92 (0.85-0.99), 0.82 (0.69-0.96), and 0.89 (0.80-0.98), respectively. In the present study, IMA and biglycan levels were found to be higher and decorin levels lower in women admitted to the hospital with threatened preterm labor and who gave preterm birth within 48 hours compared with those who gave birth after 48 hours. Conclusion In pregnant women admitted to the hospital with threatened preterm labor, the prediction preterm delivery of the combined model created by adding IMA, decorin, and biglycan in addition to the TVS CL measurement was higher than the TVS CL measurement alone. Clinical trial registration The present trial was registered at ClinicalTrials.gov, number NCT04451928.